Harmonisation, Alignment, Results : progress Report On Aid Effectiveness - OECD; World Bank (The World Bank, 2007)
The international community is committed to helping partner countries meet the Millennium Development Goal of halving global poverty by 2015. Providing more effective aid and increasing its impact on development is one important contribution to this end. This report takes stock of progress made to align donor support with developing country poverty reduction strategies, harmonise donor policies and practices to reduce transaction costs, and manage aid resources with a focus on development results. It has laid the ground for the preparation of the Paris Declaration on Aid Effectiveness endorsed by over 100 donor and developing countries at a High Level Forum in March 2005. In doing so, the signatories subscribed to some 50 specific commitments to do aid better and, for the first time, they agreed to measure progress with a set of indicators and targets. This moved the aid effectiveness agenda beyond the general consensus reached at the Rome High Level Forum in 2003 to what is now a practical blueprint for donors and partners to implement in a spirit of mutual accountability